Interactions of the Ionic Liquid [C2C1Im][DCA] with Au(111) Electrodes: Interplay between Ion Adsorption, Electrode Structure, and Stability - Yang, Juntao; Hilpert, Felix; Qiu, Yunsheng; Franz, Evanie; Briega-Martos, Valentín; Cherevko, Serhiy; Mayrhofer, Karl; Brummel, Olaf; Libuda, Jörg (Journal of Physical Chemistry C, 2024)
Modification of electrocatalysts with ionic liquids (ILs) allows us to control the activity and selectivity on the one hand but also directly affects the stability of the electrode. In this work, we studied the interaction of the IL 1-ethyl-3-methylimidazolium dicyanamide [C2C1Im][DCA] with a Au(111) surface in an aqueous electrolyte (phosphate buffer, pH 7) and the impact of the IL on the electrochemical stability of the surface. We combined complementary electrochemical in situ methods, namely, electrochemical infrared reflection absorption spectroscopy (EC-IRRAS), cyclic voltammetry (CV), electrochemical scanning tunneling microscopy (EC-STM), and online inductively coupled plasma mass spectrometry. We observe the potential-dependent and reversible adsorption-desorption of ionic species on the Au(111) surface in the potential window between 0.1 and 1.1 VRHE. We identified two types of adsorbed [DCA]− species, showing different adsorption kinetics. Already at low concentrations, the IL (10 mM) enhances the dissolution during oxidation and reduction cycles by a factor of more than 40. We observe a suppressed redeposition of dissolved Au-ions in the presence of the IL due to the formation of gold complexes with the [DCA]− anions. Our result provides molecular insights into the interplay between ionic liquid-surface interactions and surface stability.
CRIS-Team Scopus Importer:2024-03-08